1980
DOI: 10.1128/jvi.33.1.377-389.1980
|View full text |Cite
|
Sign up to set email alerts
|

Structure of murine sarcoma virus DNA replicative intermediates synthesized in vitro

Abstract: Moloney murine sarcoma virions synthesize discrete DNA products in vitro which closely resemble those found in vivo shortly after infection. These in vitro products have been isolated by electrophoresis and mapped with restriction endonucleases. In addition to the full-genome-length 6-kilobase pair linear DNA, a 5.4-kilobase pair circular DNA molecule, an incomplete linear DNA molecule, and a 600-base pair molecule were detected. The 6-kilobase pair DNA contained a 600-base pair direct terminal repeat which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
4
22
1
Order By: Relevance
“…These structures have been described previously for other retroviruses (3,12,25). One-LTR circles are apparently formed by homologous recombination between LTRs or possibly as stalled reverse transcription intermediates (8,19). Two-LTR circles form as a result of endto-end ligation of the LTR tips (38,42).…”
supporting
confidence: 64%
“…These structures have been described previously for other retroviruses (3,12,25). One-LTR circles are apparently formed by homologous recombination between LTRs or possibly as stalled reverse transcription intermediates (8,19). Two-LTR circles form as a result of endto-end ligation of the LTR tips (38,42).…”
supporting
confidence: 64%
“…precursors to the full-length plus strands, as suggested in the models proposed by Gilboa et al (7) and Dina and Benz for MuLV DNA (4). DISCUSSION Sizes of plus strands of linear retroviral DNA.…”
Section: ' Gpmentioning
confidence: 85%
“…300 nucleotides composed of sequences from both ends of viral RNA (11,23): the early plus strand might serve as the template for the synthesis of the 3' end of the minus strand, thereby producing the terminal redundancy (1,23,32). This notion has gained considerable support from the finding of plus strands equal in size and genetic content to the terminal redundancy of murine leukemia virus (MuLV) linear DNA after synthesis of MuLV DNA in detergent-disrupted virions (4,7,15).…”
mentioning
confidence: 99%
“…The circularization of purified linear viral DNA in extracts from uninfected cells provides strong evidence that 1-LTR circles are the result of host-mediated recombination between the LTRs on linear viral DNA. Alternative models, based on circular DNA molecules produced during the reverse transcription of viral RNA in permeabilized virions, have been proposed to account for the formation of 1-LTR circles (7,14). In these models, 1-LTR circles result from a circular replication intermediate that results from the failure of reverse transcriptase to catalyze displacement synthesis of the nascent viral DNA through the LTR region.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been demonstrated that the linear viral DNA synthesized in the cytoplasm is the precursor to the circular DNA forms found in the nucleus (25), the mechanism of circularization remains unknown. Circles containing one LTR have been proposed to arise either from homologous recombination between the LTRs present on the linear viral DNA molecule (13,24) or from a circular intermediate in the formation of the linear molecule during reverse transcription (7,14). Circles with two tandem LTRs, on the other hand, are presumed to arise by the direct ligation of the ends of the linear DNA molecule (15,29).…”
mentioning
confidence: 99%